Desenvolvimento, implementação e validação de um sistema de avaliação WEB (SAW) - ALCANTARA, Antonilson da Silva (2020)
Currently, the use of educational software in teaching and learning activities can be seen as a mechanism to aid the teacher, facilitating the transfer and fixation of academic content, and also is a motivating factor for the student who has in the educational software a new approach More dynamic, interactive and enables both the teacher and the student to follow the performance and evolution of the class. Therefore, identified as motivator of this work, to assist in the development of the discipline of Operating Systems (OS) in order to facilitate the understanding of content by students with subjects that are difficult to demonstrate. In order to meet these and other demands, the SAW (Web Evaluation System) system was developed, which serves as a tool for the elaboration and management of evaluative questions of the Laboratory of Operating Systems (LSO) discipline of the Bachelor's Degree in Computer Science , At the Federal University of Pará (UFPA). SAW software is an educational tool for inclusion and storage of questions with their respective answers, allowing the elaboration of simulations and evaluations, as well as registrations and changes of users of different levels of access. Stored questions have three degrees of difficulty (easy, medium, difficult), type of question (whether for simulations or evaluations) and time (in seconds) for students' responses. Evaluations and simulations are stored in a system database and can be answered by the students, each response submitted is, at the end of the simulation or evaluation, corrected by the system and the result made available to the student and to the teacher responsible for the discipline . The answers given and the number of hits are stored and reported through reports. The tool was evaluated in a group of Bachelor of Information Systems of the Federal University of Pará, obtained a positive evaluation in the questions: usability, human-computer interaction, and understanding of the tool.